Essays on the emotions - Dietz, C (2018)
In these essays, I hope to shed light on a range of basic philosophical issues concerning the emotions. To this end, I engage with many of the central ideas and questions found in philosophy of emotion over recent decades; Including, notably, the perceptual model of emotion, cognitivist theories of emotion, and questions concerning their intentional nature and epistemic role. This thesis is comprised of an introductory chapter which details the theoretical architecture that unifies this body of work, followed by four closely related essays within the philosophy of the emotions—each relating in some way to their intentional structure and epistemic significance. Among the salient influences are Timothy Williamson’s recent work in epistemology and Paul Grice’s work on the nature of reasons.